Amorphous TiS3/S/C Composite Positive Electrodes with High Capacity for Rechargeable Lithium Batteries. Issue 8 (1st January 2016) - Matsuyama, Takuya; Hayashi, Akitoshi; Hart, Connor J.; Nazar, Linda F.; Tatsumisago, Masahiro
Abstract : Composite electrodes of a -TiS3 /S/carbon (Ketjen black; KB) with high capacity were prepared by mechanical milling from a -TiS3 and S/KB composites. The composites were fabricated into coin type liquid cells and all-solid-state cells and operated as rechargeable batteries at room temperature. The reversible capacity of the coin type liquid cells decreased from 484 to 33 mAh g −1 over 50 charge-discharge cycles, because the polysulfides formed from the redox reactions of a -TiS3 /S dissolved in the liquid electrolyte. On the other hand, the all-solid-state cells showed higher reversible capacity and better cyclability than the coin type liquid cells. In order to improve their cycle performance, solid electrolyte (SE) powders were added to the composite electrodes to serve as lithium-ion conduction paths to the active materials. The cell using the a -TiS3 /S/KB composite with 30 wt% SE exhibited the highest reversible capacity of about 850 mAh g −1 at the 1st cycle and retained a reversible capacity of about 650 mAh g −1 after the 50th cycle. Owing to their relatively high sulfur content, composite positive electrodes of a -TiS3 /S/KB are attractive positive electrodes with high capacities for all-solid-state lithium secondary batteries.